PERANCANGAN FORMULIR REKAM MEDIS BENCANA DAN PENYUSUNAN STANDARD OPERATING PROCEDURE(SOP) PELAKSANAANYA DI RSUD KOTA YOGYAKARTA - , RAHMA PUSPITA, Nur Rokhman, S.Si, M.Kom. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: In disaster conditions, the hospital services will be very dense. In addition, it takes a faster service. Under conditions of very high workload, officers are required to keep documenting the service provided to the patient because of its importance as a source of data documenting that the hospital will be used for various purposes. It became the cornerstone of the needs for a data collection tool that accommodates the needs of the service during a disaster. The tool is sedemikin prepared in such a form so as to meet the needs of data and quality information to emergency conditions exist. In addition, the use of verification tools is also required form of disaster medical record so that the use of medical records form goes well. Verification tool is that the implementation procedures (SOP). Objective: This study aimed to design a disaster medical record form and Standard Operating Procedure of the implementation that can be implemented in RSUD Kota Yogyakarta. Results: disaster medical record form was chosen to triage the detailed design and presented in the form of checklists that facilitate charging when emergency conditions and flow charging / recording disaster medical record form that can be used as a verifier implementation of these activities.